PEMANFAATAN DIGITAL HR SEBAGAI STRATEGI EFISIENSI MANAJEMEN SUMBER DAYA MANUSIA DALAM RANGKA PENINGKATAN EFISIENSI KINERJA PEGAWAI - Ernawati Ernawati; Suherman Suherman; Sumiyanto Sumiyanto; Ali Rachman Banjar Nohar; Mujiarto Mujiarto; Fairizia Saputra (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
The objective of this study is to analyze the implementation of Digital HR in human resource management to improve employee performance efficiency and to explore effective strategies for its application. Using a literature review method that involves collecting, reading, and analyzing academic references such as theses and journal articles, the study found that Digital HR significantly enhances employee performance and organizational efficiency. By adopting digital systems such as Human Resource Information Systems (HRIS), artificial intelligence (AI), and e-learning platforms, companies are able to automate recruitment, performance management, and employee development processes more effectively. Effective strategies include the integration of HRIS, AI-based recruitment automation, and flexible digital training programs. Furthermore, leveraging technology for employee data management and goal-based performance systems increases transparency, identifies areas for improvement, and enables quicker feedback. The use of digital platforms for communication and collaboration also promotes employee engagement, accelerates information flow, and strengthens a positive workplace culture